Effect Of Giving Katuk Leaf Decoction (Saropus Androgynus) On Breast Milk Production In Post Partum Mothers In Sei Renggas Village - Serli Bahri; Farida Umamy; Luluk Khusnul Dwihestie; Ilma Widiya Sari (Jurnal EduHealth, 2023)
Background: breastfeeding needs the attention of mothers and health workers so that the breastfeeding process can be carried out correctly . Breastfeeding will foster a bond of love and affection between mother and newborn. Breast milk production can be increased by consuming katuk leaves in the form of Katuk leaf decoction because it contains alkoloids and sterols that can increase the smoothness of breast milk. Katuk leaves also contain vitamin A, B1, C, tannin, saponin alkaloid papaverine (Rahmanisyah, 2015) purpose: this study aims to determine the effect of giving decoction of katuk leaveson breast milk production in post partum mothers. Metode: Jenis penelitian ini kuantitatif dengan desain pre-experiment yang rancangannya menggunakan the one group pretest-posttest desaign. The population of this study were all post partum mothers in Sei Renggas village as many as 24 people. The sample in this study 21 respondents. Analysis used paired test sample t-test. Results: the results of the study post partum breast milk production before Administration of katuk leaf decoction is less breast milk production 14 respondents (66.7%) and breast milk production after administration of katuk leaf decoction is a lot of breast milk production 21 respondents (100%). Conclusion: the test results of paired t-test samples showed the value of p = 0.000 < ③ = 0.05, where Ha is accepted means that there is an effect of giving Katuk leaf decoction on breast milk production in post partum mothers in Sei Renggas village in 20211.